Resin composition, prepreg and application thereof
By using a semi-cured sheet made of a resin composition composed of epoxy resin, benzoxazine resin and filler, the problem of resin phase separation during the filling process of the semi-cured sheet at a high temperature increase speed in the prior art is solved, and an excellent filling effect on 3oz to 5oz thick copper foil is achieved.
Patent Information
- Application Number
- CN202311284780.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
During the filling process of thick copper surfaces with high temperature increase speeds, the current semi-cured sheets have too fast fluidity leading to the problem of resin phase separation, and as the thickness of the copper foil increases, the risk of resin phase separation is greater.
The semi-cured sheet made of a resin composition composed of epoxy resin, benzoxazine resin and filler is used to regulate the flowability and uniformity of the resin composition by defining the weight average molecular weight and gel time of the benzoxazine resin to avoid phase separation of the resin.
The excellent glue filling effect of the semi-cured sheet on 3oz to 5oz or even thicker copper foil at a high temperature increase rate is achieved, and problems such as resin phase separation, resin agglomeration and hollowing are avoided.
Smart Images

Figure CN119708756A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic industry, in particular to a resin composition, a prepreg and applications thereof. Background Art
[0002] Printed circuit boards (PCBs) are widely used as carriers of electronic components. The thickness of the copper foil commonly used in PCBs is currently 0.5oz to 1oz. In multi-layer PCB thick copper applications, the thickness of the copper foil needs to be greater than 3oz. However, the prepreg currently used in the PCB industry has a poor filling effect on thick copper surfaces, resulting in voids, poor dispersion, resin phase separation and other problems.
[0003] Although improving the fluidity of the prepreg can ensure the filling effect, as the requirements for thick copper in multi-layer PCBs become higher, the thickness of the copper foil increases from 3oz to 5oz, or even thicker, resulting in a higher heating rate being used during the lamination process to improve the fluidity of the prepreg to ensure the filling effect. However, as the heating rate increases, the prepreg will have the problem of resin phase separation due to faster fluidity, and as the copper foil thickness and heating rate further increase, this risk will become more and more obvious. Therefore, how to ensure the fluidity of the prepreg while preventing resin phase separation is an urgent problem to be solved. Summary of the invention
[0004] Based on this, it is necessary to provide a resin composition, a semi-cured sheet and its application to address the above problems. The semi-cured sheet made of the resin composition has excellent fluidity and does not have the problem of resin phase separation, and can ensure the filling effect of 3oz~5oz or even thicker copper foil.
[0005] According to a first aspect of the present invention, there is provided a resin composition comprising an epoxy resin, a benzoxazine resin and a filler;
[0006] The weight average molecular weight of the benzoxazine resin is 2500 to 4000, and the gel time of the benzoxazine resin at 210° C. is 100 s to 500 s.
[0007] In one embodiment, the weight average molecular weight of the benzoxazine resin is 3000-3300;
[0008] and / or, the gel time of the benzoxazine resin at 210° C. is 100 s to 300 s;
[0009] and / or, the polydispersity coefficient of the benzoxazine resin is 1 to 4;
[0010] And / or, the hydroxyl equivalent of the benzoxazine resin is 200-450.
[0011] In one embodiment, the benzoxazine resin is selected from at least one of bisphenol A benzoxazine resin, bisphenol F benzoxazine resin, DCPD benzoxazine resin, phenol benzoxazine resin, DOPO benzoxazine resin, phenolphthalein benzoxazine resin, bisphenol AF benzoxazine resin, magnolol-furfurylamine benzoxazine resin, cardanol-aniline benzoxazine resin, MDA benzoxazine resin, ODA benzoxazine resin or double bond benzoxazine resin.
[0012] In one embodiment, based on 100 parts by weight of epoxy resin, the amount of the benzoxazine resin is 80 parts by weight to 100 parts by weight, and the amount of the filler is 130 parts by weight to 160 parts by weight.
[0013] In one embodiment, the resin composition further satisfies at least one of the following conditions:
[0014] (1) The resin composition further comprises a phenolic resin;
[0015] (2) The resin composition further comprises an auxiliary agent, wherein the auxiliary agent is selected from at least one of a toughening agent, a accelerator, a flame retardant or a coupling agent;
[0016] (3) The gel time of the resin composition at 171° C. is 200 s to 400 s;
[0017] (4) The static viscosity of the resin composition is 200 Pa·s to 650 Pa·s.
[0018] In one embodiment, the phenolic resin is selected from at least one of phosphorus-containing phenolic resin, biphenyl phenolic resin or BPA-type phenolic resin;
[0019] And / or, based on 100 parts by weight of the epoxy resin, the amount of the phenolic resin is 15 parts by weight to 25 parts by weight.
[0020] According to a second aspect of the present invention, a prepreg made from the above resin composition is provided.
[0021] In one embodiment, the gel time of the prepreg at 171° C. is 160 s to 180 s;
[0022] And / or, the dynamic viscosity of the prepreg is 600 Pa·s to 1000 Pa·s.
[0023] According to a third aspect of the present invention, there is provided a circuit substrate made of the prepreg as described above.
[0024] According to a fourth aspect of the present invention, there is provided a printed circuit board made using the above-mentioned circuit substrate.
[0025] According to a fifth aspect of the present invention, there is provided a use of a prepreg as a bonding sheet in a multi-layer printed circuit board.
[0026] The resin composition of the present invention can improve the problem of large fluidity difference between the resin and the filler in the resin composition and the non-uniformity of the resin by limiting the weight average molecular weight of the benzoxazine resin and the gel time of the benzoxazine resin.
[0027] Therefore, the prepreg made of the resin composition of the present invention has a uniform surface, excellent fluidity and no resin phase separation. Furthermore, the prepreg of the present invention can not only ensure the filling effect of copper foil with a thickness of less than 3 oz, but also ensure the filling effect of copper foil with a thickness of 3 oz to 5 oz or even thicker, without the problems of resin phase separation, resin agglomeration and voids. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic diagram of the filling effect of the glue-filled board prepared by using the prepreg of Example 1 after slicing at a magnification of 250;
[0029] Figure 2 This is a schematic diagram of resin agglomeration at a magnification of 250 after slicing of a glue-filled board prepared by using the prepreg of Example 1 of the present invention;
[0030] Figure 3 This is a schematic diagram of the resin texture on the surface of the filler sheet after etching prepared by using the prepreg of Example 1 of the present invention;
[0031] Figure 4 A schematic diagram of the filling effect of the glue-filled board prepared by the prepreg of Comparative Example 3 after slicing at a magnification of 250;
[0032] Figure 5 A schematic diagram of resin agglomeration of a prepreg prepared by slicing a glue-filled board prepared by using the prepreg of Comparative Example 3 at a magnification of 250;
[0033] Figure 6 This is a schematic diagram of the surface resin texture of the glue-filled board prepared using the prepreg of Comparative Example 3 after etching. DETAILED DESCRIPTION
[0034] In order to facilitate the understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0035] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the technical field of the terminology of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.
[0036] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0037] According to a first aspect of the present invention, a resin composition is provided, comprising an epoxy resin, a benzoxazine resin and a filler; wherein the weight average molecular weight of the benzoxazine resin is 2500 to 4000, and the gel time of the benzoxazine resin at 210° C. is 100 s to 500 s.
[0038] The resin composition of the present invention can improve the problem of large difference in fluidity between the resin and the filler in the resin composition and non-uniformity of the resin by limiting the weight average molecular weight of the benzoxazine resin and the gel time of the benzoxazine resin.
[0039] Since the existing semi-cured sheet has too fast fluidity during the process of filling thick copper with glue at a high heating rate, the resin phase separation problem is easy to occur during the filling process, and as the thickness of the thick copper becomes thicker, the heating rate is higher, and the resin phase separation problem becomes more serious. The semi-cured sheet made by adopting the resin composition of the present invention has a uniform surface, excellent fluidity and no resin phase separation. Furthermore, the semi-cured sheet of the present invention can not only ensure the filling effect of copper foil with a thickness of less than 3oz, but also ensure the filling effect of copper foil with a thickness of 3oz to 5oz or even thicker. At a high heating rate, there is no generation of voids, resin phase separation, resin agglomeration and other problems.
[0040] The benzoxazine resin in the present invention is formed by prepolymerization of benzoxazine monomers. After prepolymerization, the number of hydroxyl groups in the benzoxazine resin increases, and the benzoxazine resin can react with the epoxy resin. Therefore, the reaction rate of the resin composition can be controlled by limiting the weight average molecular weight and gel time of the benzoxazine resin, thereby improving the problem of excessive difference in fluidity between the resin and the filler in the resin composition and the uneven resin. Furthermore, the prepreg made of the resin composition of the present invention can ensure the filling effect of copper foil with a thickness of 3oz to 5oz or even thicker.
[0041] Optionally, the weight average molecular weight of the benzoxazine resin is any value selected from 2500, 2700, 3000, 3200, 3300, 3500, 3700, 4000 or a range between two values, and the gel time of the benzoxazine resin at 210° C. is any value selected from 100 s, 200 s, 300 s, 400 s, 500 s or a range between two values.
[0042] In order to further improve the fluidity difference between the resin and the filler in the resin composition, the weight average molecular weight of the benzoxazine resin is preferably 3000 to 3300, and the gel time of the benzoxazine resin at 210° C. is preferably 100 s to 300 s.
[0043] In one embodiment, the polydispersity coefficient of the benzoxazine resin is 1 to 4. Optionally, the polydispersity coefficient of the benzoxazine resin is selected from any value of 1, 2, 3, 4, or a range between any two values. By limiting the polydispersity coefficient of the benzoxazine resin, the uniformity of the resin composition is further improved, and further, the filling effect of the prepreg made of the resin composition is further improved.
[0044] In one embodiment, the hydroxyl equivalent of the benzoxazine resin is 200 to 450. By limiting the hydroxyl equivalent of the benzoxazine resin, the reaction speed of the resin composition can be regulated to prevent the resin composition from reacting too fast or too slow, further improving the problem of excessive difference in fluidity between the resin and the filler in the resin composition and the problem of resin inhomogeneity. Furthermore, the prepreg made of the resin composition of the present invention has an excellent filling effect.
[0045] In one embodiment, the benzoxazine resin is selected from at least one of bisphenol A benzoxazine resin, bisphenol F benzoxazine resin, DCPD benzoxazine resin, phenol benzoxazine resin, DOPO benzoxazine resin, phenolphthalein benzoxazine resin, bisphenol AF benzoxazine resin, magnolol-furfurylamine benzoxazine resin, cardanol-aniline benzoxazine resin, MDA benzoxazine resin, ODA benzoxazine resin or double bond benzoxazine resin. Preferably, the benzoxazine resin is selected from at least one of MDA benzoxazine resin, ODA benzoxazine resin or double bond benzoxazine resin.
[0046] In one embodiment, in order to increase the resin content of the prepreg, the resin composition is based on 100 parts by weight of epoxy resin, the amount of the benzoxazine resin is 80 parts by weight to 100 parts by weight, and the amount of the filler is 130 parts by weight to 160 parts by weight, thereby increasing the resin content and further improving the filling effect.
[0047] In one embodiment, the resin composition further comprises a phenolic resin, and the amount of the phenolic resin is 15 to 25 parts by weight based on 100 parts by weight of the epoxy resin. Optionally, the phenolic resin is selected from at least one of a phosphorus-containing phenolic resin, a biphenyl phenolic resin or a BPA-type phenolic resin. By adding the phenolic resin, not only can the uniformity of the resin composition be improved by reacting with the epoxy resin, but also, according to the different selections of the phenolic resin, it can also play a role in flame retardancy or reducing dielectric constant, and then, further improve the filling effect of the semi-cured sheet made of the above-mentioned resin composition.
[0048] In one embodiment, the gel time of the resin composition at 171° C. is preferably 200 s to 400 s, more preferably 300 s to 350 s. The gel time of the resin composition is limited to this range, which can further improve the fluidity of the prepreg made of the resin composition of the present invention, so that the prepreg can better ensure the filling effect of the copper foil with a thickness of 3 oz to 5 oz or even thicker.
[0049] Optionally, the gel time of the resin composition of the present invention can also be adjusted by an imidazole accelerator. Specifically, the imidazole accelerator is selected from at least one of 2-ethyl-4-methylimidazole, 2-phenylimidazole or 2-phenyl-4-methylimidazole.
[0050] In one embodiment, the static viscosity of the resin composition is 200 Pa·s to 650 Pa·s. By limiting the static viscosity of the resin composition, it is possible to further prevent the prepreg made of the resin composition of the present invention from having resin phase separation and voids during the filling process.
[0051] In one embodiment, the resin composition further comprises an auxiliary agent, and the auxiliary agent is selected from at least one of a toughening agent, a flame retardant or a coupling agent. The present invention further improves the performance of the resin composition by adding an auxiliary agent.
[0052] Optionally, the toughening agent is selected from at least one of core-shell rubber and thermoplastic elastomer; the flame retardant is a phosphorus-containing flame retardant, and optionally, the flame retardant is selected from at least one of phosphazene compounds and organic phosphate flame retardants; the coupling agent is a silane coupling agent, and optionally, the coupling agent is selected from at least one of epoxy silane coupling agent and amino silane coupling agent.
[0053] In one embodiment, the filler has a D 50 The particle size range is 1μm~5μm, D 100The particle size range is 5μm to 10μm. By limiting the particle size of the filler, the fluidity of the filler can be regulated and the agglomeration of the filler can be prevented, thereby making the fluidity of the filler better matched with the fluidity of the resin in the resin composition, and preventing the prepreg made of the resin composition from resin phase separation during the filling process.
[0054] The filler in the present invention can be selected from at least one of fused silica, crystalline silica, spherical silica, hollow silica, alumina, talc, aluminum nitride, boron nitride, silicon carbide, barium sulfate, barium titanate, strontium titanate, calcium carbonate, and calcium silicate.
[0055] According to a second aspect of the present invention, a prepreg made of the above resin composition is provided.
[0056] In one embodiment, the gel time of the prepreg at 171°C is 160s to 180s; the dynamic viscosity of the prepreg is 600Pa·s to 1000Pa·s. By limiting the gel time and dynamic viscosity of the prepreg, the surface uniformity of the prepreg can be further improved. Furthermore, the prepreg of the present invention can not only ensure the filling effect of the copper foil with a thickness of less than 3oz, but also ensure the filling effect of the copper foil with a thickness of 3oz to 5oz or even thicker, without the generation of voids, resin phase separation, resin agglomeration and other problems.
[0057] Since the prepreg of the present invention is made of a resin composition containing epoxy resin and benzoxazine resin, preferably, the prepreg of the present invention is made of a resin composition containing epoxy resin, benzoxazine resin and phenolic resin, not only the resin content of the prepreg is increased, and the defects existing in the prepreg filling process are further improved, but also, according to different material selections, the circuit substrate made of the prepreg of the present invention also has high heat resistance, low dielectric loss and high glass transition temperature.
[0058] The preparation method of the prepreg in the present invention is:
[0059] S1, dissolving the resin composition in an organic solvent to obtain a glue solution;
[0060] S2, placing the adhesive solution on the reinforcing material and drying it to obtain the prepreg.
[0061] In step S1, the organic solvent is selected from at least one of acetone, butanone, toluene, methyl isobutyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene glycol methyl ether, and propylene glycol methyl ether.
[0062] In step S2, the reinforcing material is selected from glass fiber cloth, and the specifications of the glass fiber cloth can be selected from at least one of 7628, 2116 or 1080.
[0063] In one embodiment, the drying temperature is 160°C to 180°C.
[0064] According to a third aspect of the present invention, there is provided a circuit substrate comprising a dielectric layer and a conductive layer stacked on at least one surface of the dielectric layer, wherein the dielectric layer is formed by pressing one or at least two stacked prepreg sheets, wherein the conductive layer is preferably copper foil.
[0065] In one embodiment, the thickness of the conductive layer is greater than 0.5 oz. Optionally, the thickness of the conductive layer is 3 oz to 6 oz.
[0066] In one embodiment, the pressing conditions are: temperature 80°C to 220°C, pressure 0psi to 400psi, and time 300min to 350min.
[0067] According to a fourth aspect of the present invention, there is provided a printed circuit board made using the above-mentioned circuit substrate.
[0068] In one embodiment, the printed circuit board is made of the circuit substrate through processes such as developing, etching, drilling, degumming, copper deposition, electroplating and lamination.
[0069] According to a fifth aspect of the present invention, there is provided a use of a prepreg as a bonding sheet in a multi-layer printed circuit board.
[0070] In one embodiment, the multilayer printed circuit board includes at least two layers of printed circuit boards, and an adhesive sheet is provided between two adjacent layers of the printed circuit boards, and the adhesive sheet is a prepreg.
[0071] In one embodiment, the printed circuit board in the multilayer printed circuit board can be selected from the printed circuit board prepared in the present invention, and can also be selected from the printed circuit board purchased in the market.
[0072] Hereinafter, the resin composition and the prepreg will be further described through the following specific examples.
[0073] Example 1
[0074] In parts by weight, the resin composition of this embodiment includes 2 parts of core-shell rubber, 22 parts of phosphazene, 100 parts of epoxy resin (brand name Changchun Chemical CNE202), 155 parts of fused silica, 19 parts of phosphorus-containing phenolic resin, 90 parts of MDA-type benzoxazine resin and 0.5 parts of 2-ethyl-4-methylimidazole. The weight average molecular weight of the MDA-type benzoxazine resin is 3010, the polydispersity coefficient is 2.01, the hydroxyl equivalent is 320, and the gel time at 210°C is 182s. The gel time of the resin composition at 171°C is 310s, and the static viscosity of the resin composition is 415Pa·s.
[0075] The resin composition of this embodiment was dissolved in butanone to obtain a glue solution; glass fiber with a specification of 1080 was arranged in the above-prepared glue solution, taken out and placed in an oven at 171° C. for 3 minutes to obtain a semi-cured sheet.
[0076] The gel time of the prepreg prepared in this example at 171° C. is 160 s, the dynamic viscosity is 800 Pa·s, and the resin content in the prepreg is 72%.
[0077] Example 2
[0078] In parts by weight, the resin composition of this embodiment includes 2 parts of core-shell rubber, 22 parts of phosphazene, 100 parts of epoxy resin (brand name Changchun Chemical CNE202), 155 parts of fused silica, 19 parts of biphenylphenol, 90 parts of ODA type benzoxazine resin and 0.50 parts of 2-ethyl-4-methylimidazole, wherein the ODA type benzoxazine resin has a weight average molecular weight of 3060, a polydispersity coefficient of 1.37, a gel time of 287s at 210°C, and a hydroxyl equivalent of 446. The gel time of the resin composition at 171°C is 315s, and the static viscosity of the resin composition is 300Pa·s.
[0079] The resin composition of this embodiment is dissolved in acetone to obtain a glue solution; glass fibers with a specification of 1080 are arranged in the prepared glue solution, taken out and placed in an oven at 171° C. for 180 seconds to obtain a prepreg.
[0080] The gel time of the prepreg prepared in this example at 171° C. is 160 s, the dynamic viscosity is 761 Pa·s, and the resin content in the prepreg is 72%.
[0081] Example 3
[0082] In parts by weight, the resin composition of this embodiment includes 2 parts of core-shell rubber, 22 parts of phosphazene, 100 parts of epoxy resin (brand name Changchun Chemical CNE202), 155 parts of fused silica, 19 parts of biphenylphenol, 90 parts of double-bond benzoxazine resin and 0.50 parts of 2-ethyl-4-methylimidazole, wherein the double-bond benzoxazine resin has a weight average molecular weight of 3300, a polydispersity coefficient of 3.66, a gel time of 107s at 210°C, and a hydroxyl equivalent of 208. The gel time of the resin composition at 171°C is 301s, and the static viscosity of the resin composition is 600Pa·s.
[0083] The resin composition of this embodiment is dissolved in acetone to obtain a glue solution; glass fibers with a specification of 1080 are arranged in the above-prepared glue solution, taken out and placed in an oven at 171° C. for 150 seconds to obtain a prepreg.
[0084] The gel time of the prepreg prepared in this example at 171° C. is 180 s, the dynamic viscosity is 962 Pa·s, and the resin content in the prepreg is 72%.
[0085] Example 4
[0086] The difference between this embodiment and embodiment 1 is that the weight average molecular weight of the MDA type benzoxazine resin is 2540, the polydispersity coefficient is 1.97, the gel time at 210°C is 295s, and the hydroxyl equivalent is 300. The gel time of the resin composition at 171°C is 344s, the static viscosity of the resin composition is 324Pa·s, the prepreg prepared by baking the resin composition of this embodiment has a gel time of 168s at 171°C, a dynamic viscosity of 640Pa·s, and the resin content in the prepreg is 72%.
[0087] Example 5
[0088] The difference between this embodiment and embodiment 1 is that the weight average molecular weight of the MDA type benzoxazine resin is 3800, the polydispersity coefficient is 3.87, the gel time at 210°C is 121s, and the hydroxyl equivalent is 206. The gel time of the resin composition at 171°C is 318s, the static viscosity of the resin composition is 516Pa·s, the prepreg prepared by baking the resin composition of this embodiment has a gel time of 162s at 171°C, a dynamic viscosity of 702Pa·s, and the resin content in the prepreg is 72%.
[0089] Example 6
[0090] The difference between this embodiment and embodiment 1 is that the weight average molecular weight of the MDA type benzoxazine resin is 3000, the polydispersity coefficient is 3.01, the gel time at 210°C is 492s, and the hydroxyl equivalent is 402. The gel time of the resin composition at 171°C is 349s, the static viscosity of the resin composition is 230Pa·s, the prepreg prepared by baking the resin composition of this embodiment has a gel time of 174s at 171°C, a dynamic viscosity of 780Pa·s, and the resin content in the prepreg is 72%.
[0091] Example 7
[0092] The difference between this embodiment and embodiment 1 is that the weight average molecular weight of the MDA type benzoxazine resin is 3260, the polydispersity coefficient is 5, the gel time at 210°C is 161s, and the hydroxyl equivalent is 204. The gel time of the resin composition at 171°C is 326s, the static viscosity of the resin composition is 566Pa·s, the prepreg prepared by baking the resin composition of this embodiment has a gel time of 166s at 171°C, a dynamic viscosity of 800Pa·s, and the resin content in the prepreg is 72%.
[0093] Example 8
[0094] The difference between this embodiment and embodiment 1 is that no phosphorus-containing phenolic resin is added to the resin composition, and the amount of 2-ethyl-4-methylimidazole added is 2 parts.
[0095] The gel time of the resin composition at 171°C is 389s, and the static viscosity of the resin composition is 201Pa·s. The gel time of the semi-cured sheet made by baking the resin composition of this embodiment at 171°C is 171s, and the dynamic viscosity is 821Pa·s. The resin content in the semi-cured sheet is 72%.
[0096] Example 9
[0097] The difference between this embodiment and embodiment 1 is that 2-ethyl-4-methylimidazole is not added to the resin composition.
[0098] The gel time of the resin composition at 171°C is 600s, the static viscosity of the resin composition is 410Pa·s, the gel time of the semi-cured sheet made by baking the resin composition of this embodiment at 171°C is 180s, the dynamic viscosity is 950Pa·s, and the resin content in the semi-cured sheet is 72%.
[0099] Example 10
[0100] The difference between this embodiment and embodiment 1 is that the weight average molecular weight of the MDA-type benzoxazine resin is 3102, the polydispersity coefficient is 2.64, the gel time at 210° C. is 290 s, the hydroxyl equivalent is 500, and the amount of 2-ethyl-4-methylimidazole added is 0.7 parts.
[0101] The gel time of the resin composition at 171°C is 377s, the static viscosity of the resin composition is 432Pa·s, the gel time of the semi-cured sheet made by baking the resin composition of this embodiment at 171°C is 164s, the dynamic viscosity is 800Pa·s, and the resin content in the semi-cured sheet is 72%.
[0102] Embodiment 11
[0103] The difference between this embodiment and embodiment 1 is that the weight average molecular weight of the MDA-type benzoxazine resin is 3290, the polydispersity coefficient is 3.41, the gel time at 210° C. is 148 s, and the hydroxyl equivalent is 201.
[0104] The gel time of the resin composition at 171° C. is 310 s, and the static viscosity is 800 Pa·s. The prepreg prepared by baking the resin composition of this embodiment has a gel time of 165 s at 171° C. and a dynamic viscosity of 950 Pa·s, and the resin content in the prepreg is 72%.
[0105] Example 12
[0106] The difference between this embodiment and embodiment 1 is that the amount of 2-ethyl-4-methylimidazole added is 0.9 parts, the gel time of the resin composition at 171°C is 250s, and the static viscosity is 415Pa·s. The semi-cured sheet prepared by baking the resin composition has a gel time of 180s at 171°C and a dynamic viscosity of 300Pa·s, and the resin content in the semi-cured sheet is 72%.
[0107] Comparative Example 1
[0108] The resin composition prepared in this comparative example is prepared under the same conditions as the resin composition prepared in Example 1, except that the MDA-type benzoxazine resin has a weight average molecular weight of 2400, a polydispersity coefficient of 1.90, a gel time of 299 s at 210° C., and a hydroxyl equivalent of 306.
[0109] The resin composition of this comparative example has a gel time of 380 s at 171°C, and a static viscosity of 386 Pa·s. The semi-cured sheet prepared by baking the resin composition of this comparative example has a gel time of 182 s at 171°C, a dynamic viscosity of 615 Pa·s, and a resin content of 72% in the semi-cured sheet.
[0110] Comparative Example 2
[0111] The resin composition prepared in this comparative example is prepared under the same conditions as the resin composition prepared in Example 1, except that the weight average molecular weight of the MDA-type benzoxazine resin is 4100, the polydispersity coefficient is 3.22, the gel time at 210° C. is 100 s, and the hydroxyl equivalent is 210.
[0112] The resin composition of this comparative example has a gel time of 241 s at 171°C, and a static viscosity of 622 Pa·s. The semi-cured sheet prepared by baking the resin composition of this comparative example has a gel time of 144 s at 171°C, a dynamic viscosity of 1050 Pa·s, and a resin content of 72% in the semi-cured sheet.
[0113] Comparative Example 3
[0114] The resin composition prepared in this comparative example is prepared under the same conditions as the resin composition prepared in Example 1, except that the weight average molecular weight of the MDA-type benzoxazine resin is 3110, the polydispersity coefficient is 3.47, the gel time at 210° C. is 90 s, and the hydroxyl equivalent is 205.
[0115] The resin composition of this comparative example has a gel time of 252 s at 171°C, and a static viscosity of 622 Pa·s. The semi-cured sheet prepared by baking the resin composition of this comparative example has a gel time of 135 s at 171°C, a dynamic viscosity of 1100 Pa·s, and a resin content of 72% in the semi-cured sheet.
[0116] Comparative Example 4
[0117] The resin composition prepared in this comparative example is prepared under the same conditions as the resin composition prepared in Example 1, except that the weight average molecular weight of the MDA-type benzoxazine resin is 3050, the polydispersity coefficient is 2.11, the gel time at 210° C. is 510 s, and the hydroxyl equivalent is 310.
[0118] The resin composition of this comparative example has a gel time of 415 s at 171°C, and a static viscosity of 505 Pa·s. The semi-cured sheet prepared by baking the resin composition of this comparative example has a gel time of 190 s at 171°C, and a dynamic viscosity of 540 Pa·s. The resin content in the semi-cured sheet is 72%.
[0119] Glue filling effect test
[0120] 1. Test of the filling effect of prepreg on 3oz copper foil
[0121] (1) Low heating rate filling test
[0122] A printed circuit board with a copper foil thickness of 3 oz was used as the core board, and two prepregs obtained in the above embodiments and comparative examples were stacked on the upper and lower surfaces of the core board, and then a 0.5 oz copper foil was covered on the surface of each prepreg to obtain a glue-filled board. The glue-filled board was stacked with a stainless steel plate in correspondence up and down, sent to a vacuum press, and hot-pressed for 220 minutes according to the downstream PCB thick copper glue-filled pressing process to obtain a glue-filled board, wherein the parameters of the pressing process were: a heating rate of 1.2°C / min, a temperature of 220°C, and a pressure of 400 psi.
[0123] The filling effect and resin phase separation of the filled boards prepared with the prepregs of Examples 1 to 12 and the filled boards prepared with Comparative Examples 1 to 4 at a low heating rate were tested respectively, and the test method is as follows:
[0124] The test method for the filling effect is: after etching the copper foil on the surface of a 30cm×30cm filled board, four 10cm×10cm samples are trial-made in the middle, and after stacking them together, slices are made. The filling condition and the number of agglomerations of the cross section at a magnification of 250 are observed with SEM. If the resin filling rate is between 95% and 100%, the filling effect is good and no voids will occur. If the resin filling rate is between 90% and 95%, the filling effect is average. If the resin filling rate is below 90%, the filling effect is poor and voids will occur.
[0125] Counted by the number of agglomerates larger than 30 μm, if the number of agglomerates larger than 30 μm is less than 3, the filling effect is good, and it is considered that resin agglomeration does not occur; if the number of agglomerates larger than 30 μm is between 3 and 5, slight agglomeration occurs, and the filling effect is general; if the number of agglomerates larger than 30 μm is greater than 5, severe agglomeration occurs, and the filling effect is poor.
[0126] Performance test of resin phase separation: After etching the copper foil on the surface of the 30cm×30cm filled board, observe the phase separation on the surface after etching, measure the length of the resin phase separation lines, and take the maximum value. If the length of the maximum resin phase separation lines on the surface is less than 0.5cm, it can be determined that there is no resin phase separation. If the length of the maximum resin phase separation lines is between 0.5cm and 1cm, it is a slight resin phase separation. If the length of the maximum resin phase separation lines is greater than 1cm, it is a serious resin phase separation.
[0127] The specific test data of resin filling rate, agglomeration number and resin phase separation are shown in Table 1:
[0128] Table 1
[0129]
[0130]
[0131] According to the data in Table 1, the prepregs prepared in Examples 1 to 12 of the present invention have excellent resin filling rates compared to the prepregs prepared in Comparative Examples 1 to 4, and do not have voids and resin agglomeration. The lines of resin separation are all below 0.2 cm, and resin separation does not occur.
[0132] (2) High heating rate filling test
[0133] A printed circuit board with a copper foil thickness of 3 oz was used as the core board, and two prepregs obtained in the above embodiments and comparative examples were stacked on the upper and lower surfaces of the core board, and then a 0.5 oz copper foil was covered on the surface of each prepreg to obtain a glue-filled board. The glue-filled board was stacked with a stainless steel plate in correspondence up and down, sent to a vacuum press, and hot-pressed for 220 minutes according to the downstream PCB thick copper glue-filled pressing process to obtain a glue-filled board, wherein the parameters of the pressing process were: a heating rate of 3.5°C / min, a temperature of 220°C, and a pressure of 400 psi.
[0134] The test data of the resin filling rate, the number of agglomerates and the resin phase separation of the prepregs prepared in Examples 1 to 12 and the prepregs prepared in Comparative Examples 1 to 4 are shown in Table 2:
[0135] Table 2
[0136]
[0137]
[0138] According to the data in Table 2, the prepregs prepared in Examples 1 to 12 of the present invention have excellent resin filling rates compared to the prepregs prepared in Comparative Examples 1 to 4, and no voids or resin agglomeration occurs. The lines of resin separation are all below 0.4 cm, and no resin separation occurs.
[0139] Combining the data in Table 1 and Table 2, the prepreg prepared by the present invention also has excellent filling performance at a high heating rate and does not undergo resin phase separation, while the prepreg of the comparative example has serious resin phase separation, voids, and resin agglomeration at a high heating rate.
[0140] 2. Test of the filling effect of prepreg on 5oz copper foil
[0141] A printed circuit board with a copper foil thickness of 5 oz was used as the core board, and two prepregs obtained in the above embodiments and comparative examples were stacked on the upper and lower surfaces of the core board, and then a 0.5 oz copper foil was covered on the surface of each prepreg to obtain a glue-filled board. The glue-filled board was stacked with a stainless steel plate in correspondence up and down, sent to a vacuum press, and hot-pressed for 220 minutes according to the downstream PCB thick copper glue-filled pressing process to obtain a glue-filled board, wherein the parameters of the pressing process were: a heating rate of 3.5°C / min, a temperature of 220°C, and a pressure of 400 psi.
[0142] The present invention takes Example 1 and Comparative Example 1 as examples. Figure 1 This is a schematic diagram of the filling effect of the prepreg prepared in Example 1 at a magnification of 250; Figure 2 Schematic diagram of resin agglomeration of the prepreg prepared in Example 1 at a magnification of 250; Figure 3Schematic diagram of the resin texture on the surface of the glue-filled board after etching prepared by the prepreg of Example 1; Figure 4 This is a schematic diagram of the filling effect of the prepreg prepared in Comparative Example 3 at a ratio of 250; Figure 5 Schematic diagram of resin agglomeration of the prepreg prepared in Comparative Example 3 at a magnification of 250; Figure 6 This is a schematic diagram of the surface resin texture of the glue-filled board prepared using the prepreg of Comparative Example 3 after etching.
[0143] The test data of the resin filling rate, agglomeration number and resin phase separation of the prepregs prepared in Examples 1 to 12 and the prepregs prepared in Comparative Examples 1 to 4 are shown in Table 3:
[0144] Table 3
[0145] Resin filling rate (%) Number of reunions Resin phase separation texture (cm) Example 1 100 0 0 Example 2 100 0 0 Example 3 100 0 0 Example 4 100 1 0.3 Example 5 98 2 0 Example 6 100 0 0.3 Example 7 98 0 0.3 Example 8 98 2 0.1 Example 9 97 0 0.4 Example 10 98 1 0.3 Embodiment 11 97 0 0 Example 12 100 0 0.4 Comparative Example 1 100 6 8 Comparative Example 2 86 21 0 Comparative Example 3 89 16 1.3 Comparative Example 4 100 7 4
[0146] Combining the data in Table 3 and Figures 1 to 6 It can be seen that the prepregs prepared in Examples 1 to 12 of the present invention have a higher resin filling rate than the prepregs prepared in Comparative Examples 1 to 4, have no voids, have a small number of resin agglomerates, and the resin phase separation lines are still below 0.4 cm, and have excellent filling effects.
[0147] By comparing the data in Table 3 with that in Table 2, it can be seen that as the thickness of the copper foil increases, the filling effect decreases slightly, but it still meets the required filling effect.
[0148] 3. Test of the filling effect of prepreg on 6oz copper foil
[0149] A printed circuit board with a copper foil thickness of 6 oz was used as the core board, and two prepregs obtained in the above embodiments and comparative examples were stacked on the upper and lower surfaces of the core board, and then a 0.5 oz copper foil was covered on the surface of each prepreg to obtain a glue-filled board. The glue-filled board was stacked with a stainless steel plate in correspondence up and down, sent to a vacuum press, and hot-pressed for 220 minutes according to the downstream PCB thick copper glue-filled pressing process to obtain a glue-filled board, wherein the parameters of the pressing process were: a heating rate of 3.5°C / min, a temperature of 220°C, and a pressure of 400 psi.
[0150] The test data of the resin filling rate, the number of agglomerates and the resin phase separation of the prepregs prepared in Examples 1 to 12 and the prepregs prepared in Comparative Examples 1 to 4 are shown in Table 4:
[0151] Table 4
[0152] Resin filling rate (%) Number of reunions Resin phase separation texture (cm) Example 1 98 0 0.1 Example 2 98 0 0.1 Example 3 98 0 0.1 Example 4 99 1 0.4 Example 5 95 2 0.1 Example 6 99 0 0.4 Example 7 97 0 0.5 Example 8 96 2 0.4 Example 9 95 0 0.6 Example 10 97 1 0.5 Embodiment 11 96 0 0.1 Example 12 98 0 0.6 Comparative Example 1 100 6 10 Comparative Example 2 84 21 0.1 Comparative Example 3 87 16 2.6 Comparative Example 4 99 7 6
[0153] According to the data in Table 4, the resin filling rates of Examples 1 to 12 are all above 95%, the number of agglomerates is also within 2, and the resin phase separation lines are within 0.6 cm. Compared with the prepregs prepared in Comparative Examples 1 to 4, the filling effects of the prepregs prepared in Examples 1 to 12 of the present invention are still better than those of Comparative Examples 1 to 4.
[0154] Through the above-mentioned filling effect verification, it can be known that the prepreg prepared by the present invention can not only ensure the filling effect of copper foil with a thickness of less than 3oz, but also has a good filling effect on copper foil with a thickness of 3oz to 5oz or even greater than 5oz.
[0155] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0156] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A resin composition, characterized in that Including epoxy resin, benzoxazine resin and filler; The weight average molecular weight of the benzoxazine resin is 2500 to 4000, and the gel time of the benzoxazine resin at 210° C. is 100 s to 500 s.
2. The resin composition according to claim 1, characterized in that The weight average molecular weight of the benzoxazine resin is 3000 to 3300; And / or, the gel time of the benzoxazine resin at 210° C. is 100 s to 300 s; And / or, the polydispersity coefficient of the benzoxazine resin is 1 to 4; And / or, the hydroxyl equivalent of the benzoxazine resin is 200-450.
3. The resin composition according to claim 2, characterized in that The benzoxazine resin is selected from at least one of bisphenol A type benzoxazine resin, bisphenol F type benzoxazine resin, DCPD type benzoxazine resin, phenol type benzoxazine resin, DOPO type benzoxazine resin, phenolphthalein type benzoxazine resin, bisphenol AF type benzoxazine resin, magnolol-furfurylamine type benzoxazine resin, cardanol-aniline type benzoxazine resin, MDA type benzoxazine resin, ODA type benzoxazine resin or double bond benzoxazine resin.
4. The resin composition according to claim 1, characterized in that Based on 100 parts by weight of epoxy resin, the amount of the benzoxazine resin is 80 parts by weight to 100 parts by weight, and the amount of the filler is 130 parts by weight to 160 parts by weight.
5. The resin composition according to any one of claims 1 to 4, characterized in that The resin composition further comprises at least one of the following conditions: (1) The resin composition further comprises a phenolic resin; (2) The resin composition further comprises an auxiliary agent, wherein the auxiliary agent is selected from at least one of a toughening agent, a flame retardant, a accelerator or a coupling agent; (3) The gel time of the resin composition at 171° C. is 200 s to 400 s; (4) The static viscosity of the resin composition is 200 Pa·s to 650 Pa·s.
6. The resin composition according to claim 5, characterized in that The phenolic resin is selected from at least one of phosphorus-containing phenolic resin, biphenyl phenolic resin or BPA-type phenolic resin; And / or, based on 100 parts by weight of the epoxy resin, the amount of the phenolic resin is 15 parts by weight to 25 parts by weight.
7. A prepreg made from the resin composition according to any one of claims 1 to 6.
8. The prepreg according to claim 7, characterized in that: The gel time of the prepreg at 171° C. is 160 s to 180 s; And / or, the dynamic viscosity of the prepreg is 600 Pa·s to 1000 Pa·s.
9. A circuit substrate made of the prepreg as claimed in claim 7 or 8.
10. A printed circuit board made using the circuit substrate as claimed in claim 9.
11. Use of the prepreg as claimed in claim 7 or 8 as a bonding sheet in a multi-layer printed circuit board.